Angola : Diagnostic Trade Integration Study - World Bank (Washington, DC, 2012)
The primary goal of this Diagnostic Trade Integration Study (DTIS) is to provide a plan for reactivating Angola's productive sectors that reduces the country's reliance on imports while enabling the restoration of export capacity in the medium to long term. Executing such a plan will involve investing in the rehabilitation of infrastructure destroyed by war and making and adjusting policies that affect the institutional underpinnings of a market economy, as well as incentives for exporting and importing. This goal is inextricably linked with the overriding need to create jobs and alleviate poverty identified in the government of Angola's long-term poverty reduction plan, the Estrategia de Combate a Pobreza (ECP).